2020
DOI: 10.1101/2020.06.11.20128793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal size of sample pooling for RNA pool testing: an avant-garde for scaling up SARS CoV 2 testing

Abstract: Introduction-Timely diagnosis is essential for the containment of the disease and breaks in the chain of transmission of SARS-CoV-2. The present situation demands countries to scale up their testing and design innovative strategies to conserve diagnostic kits and reagents. The pooling of samples saves time, manpower, and most importantly diagnostic kits and reagents. In the present study, we tried to define the pool size that could be applied with acceptable confidence for testing. Material and methods- We use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Further, the pooling process can be done by pooling the nasopharyngeal/ oropharyngeal swab containing VTM samples and perform RNA extraction for pooled VTM samples [16]. The major bottleneck of RNA extraction can be removed by this method [17]. Here, we also demonstrated that pooling also works well when applied before RNA extraction by serial dilution process.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Further, the pooling process can be done by pooling the nasopharyngeal/ oropharyngeal swab containing VTM samples and perform RNA extraction for pooled VTM samples [16]. The major bottleneck of RNA extraction can be removed by this method [17]. Here, we also demonstrated that pooling also works well when applied before RNA extraction by serial dilution process.…”
Section: Discussionmentioning
confidence: 82%
“…The study showed that the extracted RNA elutes can be detected in a pool of up to 64 samples with high viral load (Ct value [16][17][18][19][20][21][22][23] in pooling prior to RT-PCR. The result correlated with the study done in Israel where a single positive RNA elute sample could be detected in pools of up to 32 samples, with an estimated false-negative rate of 10% and showed experimentally that 64 samples could be pooled together that contains enough RNA copies for detection [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations